2006
DOI: 10.1159/000096170
|View full text |Cite
|
Sign up to set email alerts
|

In Search for New Antipsoriatic Agents: NAD<sup>+</sup> Topical Composition

Abstract: The aim of the study was to examine the effectiveness of the oxidized form of nicotinamide adenine dinucleotide (NAD+), adenosine precursor, in 37 patients suffering from psoriasis. As NAD+ is known to be relatively unstable, the second goal was to establish the proper conditions for the satisfactory stability of topical NAD+ composition. In each patient, two matching plaques were selected for the study. Topical treatment with 1 or 0.3% NAD+ in Vaseline ointment admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
(17 reference statements)
0
10
0
1
Order By: Relevance
“…1-Methylnicotinamide (MNA), a major metabolite of nicotinamide (NA), has been shown recently to act in vivo as a very efficient anti-inflammatory agent [ 9 ]. After topical application of MNA, a remarkable therapeutic effect was observed in such inflammatory skin diseases as rosacea and acne vulgaris as well as in skin burns and wound healing [ 22 , 23 ]. On the other hand, MNA therapy was not effective in cases with accompanying bacterial infection, which indicates that MNA’s therapeutic effectiveness is related to its anti-inflammatory, but not anti-bacterial, properties [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…1-Methylnicotinamide (MNA), a major metabolite of nicotinamide (NA), has been shown recently to act in vivo as a very efficient anti-inflammatory agent [ 9 ]. After topical application of MNA, a remarkable therapeutic effect was observed in such inflammatory skin diseases as rosacea and acne vulgaris as well as in skin burns and wound healing [ 22 , 23 ]. On the other hand, MNA therapy was not effective in cases with accompanying bacterial infection, which indicates that MNA’s therapeutic effectiveness is related to its anti-inflammatory, but not anti-bacterial, properties [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…An opposite hypothesis links increased cellular metabolism to the increased NADH/NAD + ratio. In line with that, Wozniacka et al demonstrated that after a 4-week application of topical NAD + in Vaseline ointment administered twice daily resulted in the reduction in erythema, infiltration, and desquamation of psoriatic lesions, and was similar to the effectiveness of 0.1% anthralin [16]. However, there is a lack of comprehensive studies on real-time, in vivo non-invasive monitoring of NADH in psoriatic skin.…”
Section: Nicotinamide-adenine Dinucleotide In Psoriasismentioning
confidence: 72%
“…As a result of these mechanisms, it has been proposed that nicotinamide may prove a useful addition to the antipsoriatic repertoire and may enhance the efficacy of calcipotriene therapy when used in combination. 5 A new medication, which consists of a macrogel, polyethylene glycol-based ointment that contains calcipotriene 0.005% and nicotinamide at different concentrations (0.05%, 0.1%, 0.7%, and 1.4%), has been found to be highly stable for 24 months. In preclinical studies, the combination drug was shown to induce a significantly larger granular layer in scaly areas of mouse tail skin with abnormal maturation (95% orthokeratosis in the 0.21% nicotinamide plus 0.005% calcipotriene group vs 68% in the control group) (Dermipsor, unpublished data).…”
Section: Discussionmentioning
confidence: 99%